Are Pension Obligations, Public Office Salaries and Investment on Social Projects Hurting Fiscal Sustainability? A Panel Data Analysis of ASEAN Countries (International Journal of Psychosocial Rehabilitation, 2020)
Fiscal sustainability is the implementation of economic policies which enables the stabilization of the net value of ratio of budget deficit. This value is usually expressed as a difference among the budget expense and the budget revenue. Pension obligations, office salaries, and investment on social projects are the aspects that are crucial for any government as well as the economy of a country and they might also impact the fiscal sustainability of the country. In this context, the current study was designed in order to investigate the impact of pension obligations, office salaries and investment on social projects on fiscal sustainability in different ASEAN countries. In order to fulfill this aim, the researcher has collected data from 6 ASEAN countries i.e. Brunei, Cambodia, Indonesia, Laos, Thailand and Philippines for a period of 30 years. The major tests applied on the collected data include cross sectional dependence test, CIPS unit root test, LM Bootstrap cointegration test, AMG estimation and panel casualty test. The results obtained from these tests suggest that the impact of pension obligation, office salaries and investment in social projects on fiscal sustainability are found as significant. The theoretical and practical implications along with the limitations of the study have been discussed in the last of the study.